2021
DOI: 10.1002/ajmg.a.62086
|View full text |Cite
|
Sign up to set email alerts
|

Sleep phenotype of individuals with autism spectrum disorder bearing mutations in the PER2 circadian rhythm gene

Abstract: The Per family of genes functions as a primary circadian rhythm maintenance in the brain. Mutations in PER2 are associated with familial advanced sleep‐phase syndrome 1 (FASPS1), and recently suggested in delayed sleep phase syndrome and idiopathic hypersomnia. The detection of PER2 variants in individuals with autism spectrum disorder (ASD) and without reported sleep disorders, has suggested a role of circadian‐relevant genes in the pathophysiology of ASD. It remains unclear whether these individuals may have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 43 publications
(60 reference statements)
0
11
0
Order By: Relevance
“…Signaling by NTRK1 (TRKA) [55], cardiac conduction [56], signaling by GPCR [57], immune system [58], cytokine signaling in immune system [59], interferon signaling [60] and toll-like receptor cascades [61] were responsible for development of PD. Recent studies have shown that EGR2 [62], WNT1 [63], ARC (activity regulated cytoskeleton associated protein) [64], CHRNA7 [65], SEZ6L2 [66], IL1RAPL2 [67], PER2 [68], PCDH19 [69], CNTNAP2 [70], SLC12A5 [71], CDK5 [72], ACTL6B [73], GABRD (gamma-aminobutyric acid type A receptor subunit delta) [74], CACNA1G [75], HTR2C [76], STX1A [77], ATP1A3 [78], RIMS3 [79], CNTNAP2 [80], CDH8 [81], SCAMP5 [82], SYNGR1 [83], ARHGEF9 [84], DLG3 [85], RBP4 [86], IL9 [87], S100A9 [88], HGF (hepatocyte growth factor) [89], C3 [90], FKBP5 [91], GABRE (gamma-aminobutyric acid type A receptor subunit epsilon) [92], NCKAP1L [93], PIK3CG [94], ITGB3 [95], ANXA1 [96], SYNE2 [97] and DBI (diazepam binding inhibitor, acyl-CoA binding protein) [98] were closely involved with the occurrence, development, and prognosis of autism spectrum disorder. EGR2 [99], ADCYAP1 [100], CHRNA7 [101], NRN1 [102], ETV5 [103], STXBP1 [104], CAMKK2 [105], VAMP2 [106], SYNGR1 [107], NOD2 [108], TLR2 [109], BRCA2 [110] and LEF1 [111] were previously reported to be critical for the development of bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Signaling by NTRK1 (TRKA) [55], cardiac conduction [56], signaling by GPCR [57], immune system [58], cytokine signaling in immune system [59], interferon signaling [60] and toll-like receptor cascades [61] were responsible for development of PD. Recent studies have shown that EGR2 [62], WNT1 [63], ARC (activity regulated cytoskeleton associated protein) [64], CHRNA7 [65], SEZ6L2 [66], IL1RAPL2 [67], PER2 [68], PCDH19 [69], CNTNAP2 [70], SLC12A5 [71], CDK5 [72], ACTL6B [73], GABRD (gamma-aminobutyric acid type A receptor subunit delta) [74], CACNA1G [75], HTR2C [76], STX1A [77], ATP1A3 [78], RIMS3 [79], CNTNAP2 [80], CDH8 [81], SCAMP5 [82], SYNGR1 [83], ARHGEF9 [84], DLG3 [85], RBP4 [86], IL9 [87], S100A9 [88], HGF (hepatocyte growth factor) [89], C3 [90], FKBP5 [91], GABRE (gamma-aminobutyric acid type A receptor subunit epsilon) [92], NCKAP1L [93], PIK3CG [94], ITGB3 [95], ANXA1 [96], SYNE2 [97] and DBI (diazepam binding inhibitor, acyl-CoA binding protein) [98] were closely involved with the occurrence, development, and prognosis of autism spectrum disorder. EGR2 [99], ADCYAP1 [100], CHRNA7 [101], NRN1 [102], ETV5 [103], STXBP1 [104], CAMKK2 [105], VAMP2 [106], SYNGR1 [107], NOD2 [108], TLR2 [109], BRCA2 [110] and LEF1 [111] were previously reported to be critical for the development of bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Using functional interaction networks from the set of intersect genes, we discuss critical nodes of coalescence between biological processes related to sleep and neurodevelopment. observed in NDD patients (Hoang et al, 2021). We thus sought to investigate the interplay between sleep and rare genetic syndromes.…”
Section: Significancementioning
confidence: 99%
“…The functional mutations of NR1D1 were also detected in ASD subjects with and without sleep disorders [ 112 ]. A study by Hoang et al suggested a possible role of PER2 gene in the sleep dysregulation of ASD individuals [ 117 ]. Whole exome sequencing studies identified de novo loss-of-function variants in PER2 , RORB and CSNK1E [ 118 121 ].…”
Section: Circadian Dysfunction Mtor and Asdmentioning
confidence: 99%